CARBENDAZIN, PROCHLORAZ, PROPICONAZOLE, AND TEBUCONAZOLE TO CONTROL SOYBEAN POWDERY MILDEW - Blum, Luiz Eduardo B.; Reis, Emerson Fábio dos; Amarante, Cassandro Vidal Talamini do (Revista de Ciências Agroveterinárias, 2002)
The prevalence of powdery mildew (Microsphaera diffusa) on soybean (Glycine max) is increasing in Brazil. This fact suggests that actions to control this disease have to be taken. One of these actions is the application of fungicides. Therefore, four field experiments, in a completely randomized block design with four (tests 1 and 2) or three (tests 3 and 4) replications, were performed to evaluated the effect of fungicides against the soybean powdery mildew. These experiments were conducted in Londrina, PR (1999/2000) where soybean is constantly and extensively cultivated. The cultivar EMBRAPA 48 was used and just one application of the products was made at the growth stage R4. The treatments of Test 1 (ai = active ingredient; cp = commercial product) were: - prochloraz [450g ai/L] + propiconazole [250g ai/L] (0.5L cp/ha + 0.25L cp/ha); tebuconazole-1 [250g/L] + prochloraz (0.3+0.5); prochloraz (0.5); tebuconazole-1 (0.2); tebuconazole-2 [200g/L] (0.75); tebuconazole-1 + propiconazole (0.3+0.25); tebuconazole-1 + carbendazin-1 (0.3+0.35); propiconazole + carbendazin-1 (0.2+0.35); and the control (water). The treatments of test 2 were: carbendazin-1 (0.5); propiconazole (0.5); propiconazole (0.3); tebuconazole-1 (0.4); tebuconazole-1 + carbendazin-1 (0.4+0.3); tebuconazole-2 (0.5); carbendazin-2 [500g/L] (0.5); prochloraz (0.75); and the control (water). The treatments of the test 3 were similar to those of the test 1, but with the mixture of tebuconazole-1 + carbendazin-1 (0.24+0.25) replacing the treatment with tebuconazole-1 (0.2). The treatments of test 4 were similar to those of test 2, but the treatments with tebuconazol-1 + carbendazim-1 and prochloraz (0,75) were replaced by treatments with tebuconazole-1 (0,6) and tebuconazole-2 (0,75). The best fungicides to control powdery mildew were: test 1 - tebuconazole-2 (0.75), prochloraz + propiconazole (0.5+0.25), propiconazole + carbendazin-1 (0.2+0.35), and tebuconazole-1 + propiconazole (0.3+0.25); test 2 - carbendazin-1 (0.5), carbendazin-2 (0.5), and tebuconazole-2 (0.5); test 3 - prochloraz + propiconazole (0.5+0.25), tebuconazole-1 + prochloraz (0.3+0.5), and tebuconazole-1 + propiconazole (0.3+0.25), and; test 4 - all treatments with fungicides were efficient.